Functional Measurement of Special Education Teachers’ and Students’ Expectations Toward Job Training for Persons with Intellectual Disability - Morales-Martinez, Guadalupe Elizabeth; Lopez-Ramirez, Ernesto Octavio; Villarreal-Treviño, Maria Guadalupe; Mezquita-Hoyos, Yanko Norberto (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Persons with intellectual disability (PWID) have fewer opportunities for enrolment in school programs and post-school employment than do their peers with typical development. Evidence suggests that attitude toward PWID is a main factor in either promoting or limiting better life conditions for this population. In this paper, the goal was to determine the cognitive information integration rules underlying the expectations of 174 special education teachers and students with regard to job training for PWID. In order to accomplish this goal, four factors (Gender, Severity of disability, Type of task, and Emotional traits) were orthogonally combined to implement a cognitive algebra study design. We obtained 48 experimental conditions, with each one presented as a scenario describing a PWID in a work training situation. Participants read these scenarios and were asked to judge the probability of the success of PWID with regard to learning the skills needed to complete the required work. Patterns of response allowed us to identify low, moderate, and high viewpoints with regard to participants’ judgments of predicted success. Personal factors (Emotional traits and Severity of disability) and the Type of task factor were considered the most important in influencing the participants’ judgment. These factors seemed to be integrated in a complex systematic cognitive pattern. Implications from this type of result with regard to PWID and work training are discussed in this paper.